Tipologija esejev Iztoka Geistra - Tucovič, Vladka (Jezik in slovstvo, 2006)
The essay as an "open form" is genologically hard to determine due to its genre hybridity. Its classification seems even more difficult with its topics diverging from the generally predominant thematic domain of post-war Slovene essay writing, placed, according to Miran Štuhec (2003: 7), in the triangle of "humans - literature - nation". In the case of essays on nature by Iztok Geister, the article concludes that a typological approach to the corpus of essays in seven books by Geister is possible on the basis of researching linguistic style or narrative features of the essays on nature, from which follows that his essays can be classified as journalistic, popular-science and "artistic" essays, while the latter can be further divided into poetic and (thematically more accurate) travel essays.
Keywords: eseji; Geister; Geister, Iztok; Slovene literature; slovenska književnost; slovenska proza; tiplogija